PENGARUH MEDIA BUKU CERITA BERGAMBAR TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS IV SDN 3 REMPEK TAHUN AKADEMIK 2023/2024 - Juniati; Habiburahman, Lalu; Hadi, Mashal (Literasi: Jurnal Pendidikan Guru Indonesia, 2024)
This research aims to improve the reading comprehension skills of class IV students at SDN 3 Rempek. This research was carried out at the Rempek 3 elementary school. The number of samples in this study was 1 class with 14 students and female students. This research is quantitative research, namely research that is used to process number-based data. This research is quantitative with pre-experimental methods. The experimental research method is a quantitative method, used if the researcher wants to conduct an experiment to find the effect of independent variables (influence) on dependent variables (influence) under controlled conditions. Data collection techniques in this research use observation and documentation techniques. Data collection instruments for carrying out the initial test (pretest) and carrying out the final test (posttest) the results of this research are: Based on the pretest data analysis, there are 8 students who are classified in the high category with a percentage of 57%, 6 students who are classified in the medium category with a percentage of 43% . Based on posttest data analysis, there were 12 students who got a score of 75 in the very high category with a percentage of 86%, 2 students were in the high category who got a score of 74 with a percentage of 14% of the total sample. The total number of average pretest scores obtained was 18,286 and the total number of average posttest scores obtained was 21,357. The range of scores between the pretest and posttest scores is 3,071 and the total range between the average pretest and posttest scores if squared is 9,433